A Novel Heterozygous Mutation in the STAT1 SH2 Domain Causes Chronic Mucocutaneous Candidiasis, Atypically Diverse Infections, Autoimmunity, and Impaired Cytokine Regulation - Meesilpavikkai, Kornvalee; Dik, Willem A.; Schrijver, Benjamin; Nagtzaam, Nicole M. A.; van Rijswijk, Angelique; Driessen, Gertjan J.; van der Spek, Peter J.; van Hagen, P. Martin; Dalm, Virgil A. S. H. (Frontiers in Immunology, 2017)
Chronic mucocutaneous candidiasis (CMC) is a primary immunodeficiency (PID) characterized by persistent or recurrent skin and mucosal surface infections with Candida species. Different gene mutations leading to CMC have been identified. These include various heterozygous gain-of-function (GOF) mutations in signal transducer and activator of transcription 1 (STAT1) that are not only associated with infections but also with autoimmune manifestations. Recently, two STAT1 GOF mutations involving the Src homology 2 (SH2) domain have been reported while so far over fifty mutations have been described mainly in the coiled-coil and the DNA binding domains. Here we present two members of a Dutch family with a novel STAT1 mutation located in the SH2 domain. T lymphocytes of these patients revealed STAT1 hyperphosphorylation and higher expression of STAT1 target genes. The clinical picture of CMC in our patients could be explained by diminished production of interleukin (IL)-17 and IL-22, cytokines important in the protection against fungal infections.